DORNASE ALFA: WHAT EFFECTIVENESS OF MEDICATION DEPENDS ON? - O.I. Simonova ("Paediatrician" Publishers LLC, 2009)
The treatment with dornase alfa (Pulmozyme) plays one of the key roles in basic treatment of cystic fibrosis as in children as in adult patients. But effectiveness of this medication depends on different important constituents, starting from its proper administration, to precise execution of intake rules. The article earnestly shows that effectiveness of dornase alfa in many respects depends on proper fulfillment of kinesitherapy. Different rational schemes of drug intake combined with individual types of kinesitherapy exercises were presented.Key words: children, cystic fibrosis, dornase alfa, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):130-135)